\( \left. \begin{array} { l } { \rightarrow 2 \log ( x ) + \log ( y ) = 2 } \\ { \rightarrow \log ( x ) - \log ( y ) = 1 } \end{array} \right. \)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Extra Insights
To solve the system of equations, we can use properties of logarithms. From the second equation, \( \log(x) - \log(y) = 1 \) can be rewritten using the quotient rule of logarithms as \( \log\left(\frac{x}{y}\right) = 1 \). This means \( \frac{x}{y} = 10 \), leading to \( x = 10y \). Now, substitute \( x = 10y \) into the first equation: \( 2\log(10y) + \log(y) = 2 \) simplifies to \( 2(\log(10) + \log(y)) + \log(y) = 2 \). Since \( \log(10) = 1 \), we have \( 2(1 + \log(y)) + \log(y) = 2 \) or \( 2 + 2\log(y) + \log(y) = 2 \). This simplifies to \( 3\log(y) = 0 \), hence \( \log(y) = 0 \) leading to \( y = 1 \). Finally, substituting back gives \( x = 10(1) = 10 \). Therefore, the solution to the system is \( x = 10 \) and \( y = 1 \). Happy math-ing! You’ve turned logarithmic land into a puzzle that’s been solved! 🎉📚